Analysis of Li distribution in ultrathin all-solid-state Li-ion battery (ASSLiB) by neutron depth profiling (NDP). Issue 3 (3rd March 2020) - Tomandl, I.; Vacik, J.; Kobayashi, T.; Mora Sierra, Y.; Hnatowicz, V.; Lavreniev, V.; Horak, P.; Ceccio, G.; Cannavo, A.; Baba, M.; Ye, R.
Abstract : Lithium-ion batteries are promising energy storage technology devices. They possess many advantages, including high energy density, flexible and lightweight construction and considerable durability. The rapid development of nanotechnologies can further improve their capacity, cycle life and safety. In this experiment, Li-ion diffusion in an all-solid lithium-ion battery (ASSLiB) was studied using the Neutron Depth Profiling (NDP) nuclear analytical technique. The thin ASSLiB system was synthesised by RF magnetron sputtering. The experiment showed that NDP is a very efficient experimental tool for direct analysis of Li distribution in Li batteries. It has been found that the depth profile of Li strongly depends on the state of charge of the battery. About one-third of the total number of Li in ASSLiB can move between the electrodes during charging / discharging. It has been also shown, using the multipixel detectors, that the lateral distribution of Li in ASSLiB is not homogeneous. This can mean, for example, that the position of Li is affected by structural defects that may arise due to variation of the volume or stress of the battery during charging or discharging. In the work are presented first results of measurements performed on ASSLiB of a 1 µm thickness.